The Anxious Heart of Injustice: Negative Affective Responses to Disabilities - Beaudry, Jonas-Sébastien (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
It appears that liberal thought pays too little attention to negative affective responses toward people with disabilities. As a result, liberal theories may lack corrective structures to deal with such emotions and theorists themselves may fall prey to their influence. Assuming these troubling suggestions are at least partly well-founded and thereby warrant closer investigation, I examine three hypothetical causes of this state of affairs: the philosophical distrust toward emotions, the failure to attend to anxious reactions toward anomalous bodies, and the fear of vulnerability connected to liberal ideology. Although the causal factors that I discus are difficult to demonstrate empirically, they are nonetheless intuitively compelling.